Peran Kenyamanan dalam Memediasi Pengaruh Atmosfer dan Social Media Influencer terhadap Minat Berkunjung di Tahoma Coffee and Eatery - Lestari, Ni Wayan Marchella Ernita; Mahyuni, Luh Putu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study is aimed at analyzing the influence of atmosphere and social media influencers on consumers' intention in visiting Tahoma Coffee and Eatery, as well as the role of convenience as a mediating variable. The target population in this study is consumers of Tahoma Coffee and Eatery, and through convenience sampling we obtained 75 followers as respondents. Data was collected using a questionnaire and analyzed using the Structural Equation Modeling (SEM) approach via SmartPLS. The findings show that there is a partially significant positive relationship between atmosphere and social media influencers on consumer comfort and visit intention. It can also be seen that comfort is able to influence intention in visiting in a significant positive way. Not only that, the findings also confirm that comfort contributes to the atmosphere and social media influencers partially to interest in visiting. Through these findings, it can be suggested to Tahoma Coffee and Eatery managers to maximize store elements such as atmosphere, social media influencers, and comfort to increase interest in visiting. Next researchers can add samples, study objects, and research variables